The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1128/aac.01078-06
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific Reduction of Oxidative and Lipid Metabolism in Adipose Tissue of 3′-Azido-3′-Deoxythymidine-Treated Rats

Abstract: Although it is well accepted that treatment with some nucleoside reverse transcriptase inhibitors modifies both fat metabolism and fat distribution in humans, the mechanisms underlying these modifications are not yet known. The present investigation examined whether a decrease in oxidative capacity, induced by a chronic oral administration of 3-azido-3-deoxythymidine (AZT) in rats, could be associated with an alteration of the lipogenic capacity of white adipose tissues. The impact of obesity as a factor was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 37 publications
2
8
1
Order By: Relevance
“…For example, investigations by Petit and colleagues [70] have revealed that NRTIinduced mitochondrial DNA depletion in cultured human adipose tissue is accompanied by a proportional reduction in ATP production and mitochondrial respiration rates, indicating that even small changes in adipocyte mitochondrial DNA levels can have important effects on cell function [70]. Similar results have been obtained in studies of zidovudine-treated rats, in which adipose tissue mitochondrial DNA depletion and respiratory function were highly correlated in the subcutaneous fat depot but not in visceral fat [71]. In this study, zidovudine was also found to activate AMP kinase, a key regulator of adipose energy status that seeks to conserve energy (in the form of ATP) by limiting fatty acid efflux from adipocytes and favouring local fatty acid oxidation [72].…”
Section: Antiretroviral Therapy-associated Lipoatrophysupporting
confidence: 60%
“…For example, investigations by Petit and colleagues [70] have revealed that NRTIinduced mitochondrial DNA depletion in cultured human adipose tissue is accompanied by a proportional reduction in ATP production and mitochondrial respiration rates, indicating that even small changes in adipocyte mitochondrial DNA levels can have important effects on cell function [70]. Similar results have been obtained in studies of zidovudine-treated rats, in which adipose tissue mitochondrial DNA depletion and respiratory function were highly correlated in the subcutaneous fat depot but not in visceral fat [71]. In this study, zidovudine was also found to activate AMP kinase, a key regulator of adipose energy status that seeks to conserve energy (in the form of ATP) by limiting fatty acid efflux from adipocytes and favouring local fatty acid oxidation [72].…”
Section: Antiretroviral Therapy-associated Lipoatrophysupporting
confidence: 60%
“…HAART with HH induced negative observational changes in the body weight of experimental animals, mostly marked in the diabetic + HAART + HH (100 and 200 mg/kg) animals. While loss of weight may be associated with induction of diabetes, initiation of HAART may as well contribute to the low pace of weight gain due to other metabolic activities relative to lipid and sugar [41].…”
Section: Discussionmentioning
confidence: 99%
“…For example, AZT is known to inhibit replication of mitochondrial DNA and biogenesis of mitochondria in adipocytes. Decreased numbers of mitochondria adversely affect functions of the adipose tissues [118]. Similarly, HIV protease inhibitors (PI) often cause cellular stress, inhibit the normal differentiation process of adipocytes and reduce fat storing capacity of the body [119].…”
Section: Haart Il-18 and Halsmentioning
confidence: 99%